Primary mucinous carcinoma of the skin with co-expression of TRPS1 and GATA3: a case report - Song, Liling; Zhu, Ning; Jiang, Lei; Gao, Dong; Yu, Guohua (Frontiers in Oncology, 2025)
Primary cutaneous mucinous carcinoma (PCMC) is a rare malignant neoplasm, with approximately 450 cases reported worldwide to date. Its histological features closely resemble those of mucinous carcinoma of the breast, posing significant diagnostic challenges. We report a case of PCMC occurring at the upper margin of the eyelid in a 65-year-old male who presented with a painless, progressively enlarging mass over a four-year period. Histopathological examination following surgical excision confirmed the diagnosis of PCMC, with immunohistochemical staining demonstrating co-expression of TRPS1 and GATA3. This case highlights several key clinical and pathological characteristics of PCMC. The tumor typically affects middle-aged to elderly males and demonstrates low metastatic potential but a high rate of local recurrence. Histologically, it is difficult to distinguish from cutaneous metastatic mucinous carcinoma (MMC), particularly of breast origin. In this context, the co-expression of TRPS1 and GATA3 necessitates careful interpretation, as these markers are not exclusive to PCMC. The diagnostic utility of TRPS1 lies not in its individual specificity, but rather in its combined use with other markers such as GATA3. Radical surgical excision remains the mainstay of treatment, with adjuvant endocrine therapy considered in ER/PR-positive cases. Compared to cutaneous MMC, PCMC generally carries a more favorable prognosis, reinforcing the importance of early and accurate diagnosis. Ultimately, the diagnosis of PCMC relies on a comprehensive evaluation that integrates clinical presentation, imaging findings, histological architecture, and immunohistochemical profiles.